Kompetencje polskich całodobowych opiekunów osób starszych w Niemczech. Wyzwania edukacyjne (wybrane wyniki badań sondażowych) - Ignatzi, Helene; Piorunek, Magdalena; Tyrach, Martina (Kultura-Społeczeństwo-Edukacja, 2025)
The text presents selected results of a survey conducted among live-in-caregivers from Poland working with the older adults in Germany (the research sample consisted of 119 individuals). These results are a part of the Polish-German research project focusing on caregivers’ management of their tasks. The article discusses a research section designed to obtain answers to questions in which the caregivers were asked to self-assess their competencies as live-in caregivers from Poland working in Germany. The respondents were asked to assess their competencies in caring for persons with dementia, nursing, accompanying individuals in the process of dying and death, linguistic competencies, the ability to carry out their tasks, the traits and qualities caregivers are expected to show to cope with these tasks, as well as their trainingand education-related needs. The results demonstrate educational needs the respondents have to address, even though in general they hold relatively high opinion of their competencies; this claim, however, upon closer examination of the individual competencies, sounds too optimistic.